Effects of production system on the gut microbiota diversity and IgA distribution of Kampong chickens, Indonesia - R. SUSANTI; WULAN CHRISTIJANTI (Society for Indonesian Biodiversity, 2022)
Abstract. Susanti R, Christijanti W. 2022. Effects of production system on the gut microbiota diversity and IgA distribution of Kampong chickens. Biodiversitas 23: 1082-1090. Native chickens (Kampong chickens) are poultry in Indonesia that is raised using a traditional production system. This study aimed to analyze the differences of the Kampong chicken production system (extensive/E and semi-intensive/SI) on the diversity and abundance of gut microbiota and the distribution of IgA. Each sample of Kampong chickens was slaughtered, then their thoracic and abdominal cavities were dissected, and their intestines were collected. Furthermore, the intestinal tissue was processed to make histological preparations for immunohistochemical analysis of IgA. Gut contents of 25 g were taken aseptically and used for next-generation sequencing (NGS) and GC-MS analysis. The results showed 12 bacterial phyla in the intestines of SI and E chicken. E chickens had a higher abundance and diversity of microbiota than the SI chickens. The phylum Firmicutes dominated the E and SI chickens' gut microbiota (>50%). SI chickens have a higher Firmicutes/Bacteroidetes ratio than the E chickens. The SIgA distribution showed an IRS score of 4 (moderate), both in E and SI chickens. It was concluded that the production system affects the intestinal microbiota's abundance and diversity but not on the intestine IgA of Kampong Chickens. This study highlights that based on the Firmicutes/Bacteroidetes ratio, the semi-intensive system is more suitable for Kampong chicken meat and eggs than the extensive system.